2015 APWG Symposium on Electronic Crime Research (eCrime) 2015
DOI: 10.1109/ecrime.2015.7120798
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of content copyright infringement in mobile application markets

Abstract: As mobile devices increasingly become bigger in terms of display and reliable in delivering paid entertainment and video content, we also see a rise in the presence of mobile applications that attempt to profit by streaming pirated content to unsuspected end-users. These applications are both paid and free and in the case of free applications, the source of funding appears to be advertisements that are displayed while the content is streamed to the device.In this paper, we assess the extent of content copyrigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Similarly, many smartphone applications have been reported to illegally stream copyrighted content [40]. It has been noted that users of such streaming applications are exposed to numerous threats, ranging from annoying ads to very serious ones [41].…”
Section: Streaming Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, many smartphone applications have been reported to illegally stream copyrighted content [40]. It has been noted that users of such streaming applications are exposed to numerous threats, ranging from annoying ads to very serious ones [41].…”
Section: Streaming Applicationsmentioning
confidence: 99%
“…As an example, after the Paris terror attacks of 2015, security analysts found that terrorists could have used PlayStation 4 as the way to exchange messages without being discovered [39]. Similarly, many smartphone applications have been reported to illegally stream copyrighted content [40]. It has been noted that users of such streaming applications are exposed to numerous threats, ranging from annoying ads to very serious ones [41].…”
Section: Related Workmentioning
confidence: 99%